WHO's support for COVID-19 research and knowledge management in the Eastern Mediterranean Region. (24th June 2022) - Rashidian, Arash; Wu, Kaiyue; Al Ariqi, Lubna; Aly, Eman; Mandil, Ahmed; Barakat, Amal; Kodama, Chiori; Kheirandish, Mehrnaz; Nour Eldin Hassan, Hatem; Doctor, Henry Victor; Hemachandra, Nilmini; Fahmy, Kamal; et al.
Abstract : Health research, innovation and knowledge management remain major priorities of the WHO's response to the COVID-19 pandemic. WHO's Eastern Mediterranean Regional Office (EMRO) supports priority research initiatives that address gaps in current knowledge regarding the COVID-19 pandemic. Through a specific call for proposals, 122 research proposals were received and reviewed in 2020, of which 17 were recommended for funding from eight countries. Ten countries in the region participated in the global solidarity trial to assess potential therapies for COVID-19. In addition, WHO advocated for early serological and epidemiological investigations ('COVID-19 Unity Studies') on the general population, healthcare workers, pregnant women and neonates, and extending technical, financial and material support for them. Starting in early 2020, scholarly articles on COVID-19 have been published in every issue of the Eastern Mediterranean Health Journal . More than 6300 publications on COVID-19 were made available on the WHO knowledge management portal in the last year alone. WHO is also supporting countries in conducting studies to assess the field effectiveness of vaccines deployed nationally. To build and strengthen country capacities, regional webinars and intercountry meetings were conducted on research ethics, national health information systems and evidence-based health policy making. With support from WHO EMRO's new research and knowledge management pillar, countries in the region were well equipped to contribute to a global understanding of the novel virus's characteristics, as well as employ a national response based on informed evidence.